THE COMPARISON OF UZBEK AND ENGLISH POETRY - Aliyev Akmal Ikromjonovich, (World Scientific Research Journal, 2025)
Abstract. This paper compares Uzbek and English poetic traditions across history, form, prosody, thematic concerns, and translation practice. It traces continuities from classical Uzbek divan poetry (with Alisher Navoi as a focal figure) to twentieth-century and contemporary Uzbek verse, and contrasts these with the development of English poetry from medieval lyric and Chaucerian meters through the sonnet tradition to modern free verse. The comparative section highlights how linguistic typology (syllable-timed Uzbek vs. stress-timed English), formal conventions (ghazal/qasida/muhammas vs. sonnet/iambic meter/blank verse), and differing cultural functions (courtly/Sufi devotion and national identity in Uzbek poetry; individual lyric subjectivity, narrative and dramatic uses in English) shape poetic technique and translation choices. Practical recommendations for translators and editors preparing Uzbek ↔ English poetry for international journals are offered.